PEMBELAJARAN KOOPERATIF INVESTIGASI KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX SMP NEGERI 1 TEMBILAHAN - Anita Anita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
This study aims to improve the ability of mathematics learning outcomes of IX students with the application of cooperative learning investigations. The research subjects were 32 students of class IX SMP Negeri 1 Tembilahan. This research is a classroom action research with the application of cooperative investigative learning steps, namely: 1) Introduction which consists of conditioning students to be ready to learn, conveying learning objectives, providing motivation, giving an explanation of the learning model used. 2) Activities, namely grouping, students are divided into study groups and at the investigation stage, students are given problems related to teaching material. 3) Refecting. The results showed an increase in student learning, namely 77.42% in the first cycle to 93.55% in the second cycle. The percentage of teacher activity observations increased from 85.33% in the first cycle to 95.66% in the second cycle. The percentage of observations of student activities increased from 82.44% in the first cycle to 91.27% in the second cycle. This showed that the activities of teachers and students in cooperative learning group investigations went very well. Student responses to cooperative learning group investigations in this study were very positive.